Implementasi Metode Storytelling dalam Menanamkan Nilai Kejujuran Dan Empati pada Anak - Adriana Susanti Nona Ina (Institut Agama Islam Riyadhlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2026)
Character education is an important aspect of early childhood development. The values ​​of honesty and empathy need to be instilled from an early age so that children can develop positive social behavior and show concern for others. One effective learning method for instilling these values ​​is storytelling. This study aims to analyze the implementation of the storytelling method in instilling the values ​​of honesty and empathy in early childhood through a literature review of thirty relevant scientific journal articles. This study used a literature review method with descriptive analysis techniques on various research findings related to storytelling, character education, honesty, and empathy in early childhood. The results of the study indicate that storytelling is an effective learning method in character education because through stories, children can understand moral values ​​more concretely through the characters, plot, and moral message conveyed. Furthermore, storytelling has also been shown to increase children's empathy skills, help children understand the feelings of others, and foster an honest attitude in everyday life. Thus, storytelling can be an effective learning strategy in instilling character values ​​in early childhood.